What's Changing: Population Size or Land-Use Patterns? The archaeology of Upper Mangrove Creek, Sydney Basin - Attenbrow, Val (Terra Australis, 2006)
The Upper Mangrove Creek catchment was an ideal locality in which to undertake field investigation into Aboriginal use of the coastal hinterland. The area, 101 square kilometres in size, is rich in sites that provided significant archaeological evidence of Aboriginal use of the coastal hinterland. The catchment became the focus of major archaeological salvage work in the late 1970s, prior to the construction of the Mangrove Creek Dam. Further research, undertaken by Val Attenbrow, on the total catchment expanded upon the results of earlier work. This monograph describes the later research project and summarises the salvage program results. This evidence is used by the author to explore current research issues relating to the interpretation of the mid- to late-Holocene archaeological record in Australia, particularly quantitative changes relating to population numbers and aspects of human behaviour, such as risk management, subsistence, mobility and land-use patterns.